Nickel-doped lanthanum cerate nanomaterials as highly active electrocatalysts - Butt, Tehmeena Maryum; Erum, Safia; Mujtaba, Ayesha; Medvedev, Dmitry; Janjua, Naveed Kausar (Frontiers in Chemistry, 2022)
The efficient oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) catalyst materials are crucial in energy research domain due to the properties tunability. The structural modification in perovskites, lanthanum cerates (LaCeO3) upon doping at A- or B-sites significantly affects the surface activity and enhances the catalysis efficacy. Herein, B-site nickel-doped lanthanum cerate; LaCe1-xNixO3±δ nanopowders were applied in high-temperature (HT) electrochemical impedance spectroscopy (EIS) for solid-oxide fuel cell (SOFC) tests as the ORR indicators and for the cyclic voltammetric OER investigations in alkaline medium. The integration in SOFC applications via solid-state EIS in co-pressed three-layered cell with LCNiO as cathode, is investigated in oxygen-methane environment which reveal the augmented conductivity with temperature (700-850 °C). The higher electrokinetic parameters, including diffusion coefficients, Do heterogeneous rate constant, ko and peak current density for OER in KOH-methanol at LCNiO-9 modified glassy carbon (GC) electrode imply a robust gauge of catalytic performance. CV indicators and EIS conductivities of LaCe1-xNixO3±δ nanomaterials refer to the promising potencies in electrocatalytic energy applications.